Recurrence of tumoral calcinosis: a case report - Sandomenico, Fabio; Corvino, Antonio; Ronza, Francesco Michele; Catalano, Orlando; Fazioli, Flavio; De Chiara, Anna; Campanino, Maria Raffaela; Porcaro, Mauro; Tafuri, Domenico; Petrillo, Antonella (Acta Biomedica Atenei Parmensis, 2019)
We describe radiographic, contrast-enhanced MDCT and MRI findings with pathologic correlations of an unusual recurrence of tumoral calcinosis, also called Teutschlander disease. The disease was silent in the first decade of life, when it appeared with elbows recurring lesions, until the seventh decade of life, when a left hip active growth lesion developed. A review about tumoral calcinosis pathogenesis, clinical course and imaging differential diagnosis is reported. (www.actabiomedica.it)